دراسة تقييمية حول أهداف المنهج الدراسي لمقارنة الأديان التي تقدمها شعبة اللسانيات من جامعة جنوب شرق سريلانكا : Evaluation Study on the Objectives of the Comparative Religious Study Offered by the Linguistics Unit of the South Eastern University of Sri Lanka - MHA. Munas; AMM. Hijas (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص إن صياغة الأهداف للمنهج الدراسي احتلت حيزا كبيرا في المجال التربوي حيث يتوقف عليها نجاح عملية التعليم الفعال. فمن الأهداف، تستقى تفاصيل محتويات المقرر الدراسي بالإضافة إلى أن تنظيم الحصة الدراسية يجري على أساس أهداف المادة والتوافق بين أهداف المنهج الدراسي والمهارات المنشودة لدى الخرجيين أمر لا غنى عنه. أما المنهج الدراسي لدراسة مقارنة الأديان التي يقدمها شعبة اللسانيات فى جامعة جنوب شرق سريلانكا فلم يتعرض للمراجعة بالرغم من أنه قد مر عليه أكثر من خمس سنوات من الإعداد مما يستلزم القيام بمراجعة فورية، وعلى هذا فهذا البحث يركز على استطلاع آراء خريجي اللسانيات حول المنهج الدراسي لمادة مقارنة الأديان مستهدفا إلى الكشف عن مدى توافق أهدافها مع محتويات مقارنة الأديان مع تقديم الحلول المناسبة لسد الفجوة بأصحاب القرار. وقد استخدم الباحثون المنهج الوصفي التحليلي للمعلومات التي حصل عليها عن طريق الاستبانة والمقابلة فاستنتج الدراسة ان هناك فجوة عظيمة بين أهداف المنهج وتفاصيل محتوياته والتي فقد أثرت تأثيرا سلبيا على خريجى اللسانيات حتى إنهم يواجهون مشاكل في الحصول على وظيفة مناسبة. Abstract The designing of goals for the curriculum occupied a large area in the field of education, as the success of the effective teaching process depends on it. From the objectives, the course contents are derived, in addition to the fact that the lesson is organized on the basis of the objectives of the subject, and the compatibility between the objectives of the curriculum and the skills desired by the graduates is indispensable. As for the curriculum for the comparative religion subject offered by the Linguistics unit at the South Eastern University of Sri Lanka, it has not been reviewed, although more than five years of preparation have passed. How much does it need an immediate review? This research focuses on surveying the opinions of linguistics graduates about the curriculum of comparative religions subject, with the purpose of revealing the compatibility of their objectives with the subject, while evaluating the appropriate solution to fill the gap by those who possess soundness in this regard. The researchers used the descriptive analytical methodology to the data obtained through the questionnaire and the interview. The study proved that there is a gap between the objectives of the curriculum and the course content, which has negatively affected linguistics graduates that they face plenty of problems related to job seeking.